Single-cell transcriptome profiling reveals enriched memory T-cell subpopulations in hypertension - Wang, Xiaoqi; Wu, Xiaobin; Zhang, Pei; Zhou, Yuan; Cai, Jun; Jin, Ling (Frontiers in Cell and Developmental Biology, 2023)
The adaptive immune response mediated by T cells plays a vital role in the initiation and maintenance ofblood pressure (BP) elevation. Memory T cells,which are antigen-specific T cells, can response specifically towards repeated hypertensive stimuli. Although the roles of memory T cells in animal models are well studied, their maintainance and functions of them in hypertensive patientsare poorly understood.Here, we focused on the circulating memory T cells of hypertensive patients. By using single cell RNA sequencing technology, subsets of memory T cells were identified. Differentially expressed genes (DEGs) and functional pathways wereexploredfor related biological functions in each population of memory T cells. Our work identified four subsets of memory T cells in the blood of hypertensive patients, with CD8 effector memory T (TEM) cells accounting for more cells and demonstrating more biological functions than CD4 TEM cells. CD8 TEM cells were further analyzed using single cell RNA sequencing technology, and subpopulation 1 was demonstrated to contribute to BP elevation. The maker genes CKS2, PLIN2 and CNBP were identified and validated by mass-spectrum flowcytometry. Our data suggest that CD8 TEM cells as well as the marker genes could be preventive targets for patients with hypertensive cardiovascular disease.